Searching for new perspectives? Towards entrepreneurial orientation and the inclusion of the provider perspective in current information systems research - Antonia Köster; Natalie Kaltenecker; Thomas Hess (Ludwig-Maximilians-Universität München, Institut für Wirtschaftsinformatik und Neue Medien (WIM), 2015)
[Introduction ...] The remainder of this study is structured as follows: Section two provides the theoretical background and defines EO, the research objects, and research perspectives. In section three, we report on the procedures of our scientometric analysis. Results are presented in section four. In section five, we give a summary of our overall findings, discuss the results from our analysis and provide avenues for further research.
Keywords: 650; Wirtschaftsinformatik; Forschung; Bibliometrie